2001
DOI: 10.1055/s-2001-11332
|View full text |Cite
|
Sign up to set email alerts
|

Individual Anaerobic Threshold: Methodological Aspects of its Assessment in Running

Abstract: The present study was designed in order to examine the objectivity and reliability of the individual anaerobic threshold (IAT) as well as its resistance against several interfering factors: missing exhaustion, preliminary exercise, longer step duration, and lower speed increment. 87 male and 24 female runners and triathletes were examined. They performed both the original test procedure (IAT(3/2); 3 min step duration, 2 km x h(-1) increment until volitional exhaustion) and either a retest or one of several alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 24 publications
1
33
0
1
Order By: Relevance
“…Previous studies demonstrated V peak is a reliable variable in a test-retest protocol, with high intraclass correlation coe cient and low bias risk [18][19][20] . However, these studies measured V peak in association with VO 2max (i.e., using gas analysis mask) and blood collection (i.e., to assess lactate threshold).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies demonstrated V peak is a reliable variable in a test-retest protocol, with high intraclass correlation coe cient and low bias risk [18][19][20] . However, these studies measured V peak in association with VO 2max (i.e., using gas analysis mask) and blood collection (i.e., to assess lactate threshold).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that HR at submaximal stages has a high reliability; however, their values tend to be lower in the re-test 20,[24][25][26] , possibly due to a subjects' familiarization to the protocol 25 . Nevertheless, in the present study, the tests protocols (i.e., with or without the mask) were performed in a randomized order, reducing potential bias associated with this factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Longer stages may decrease variance in speed at particular markers between test-retest trials. It is likely that prolonged stages allow stabilisation between arterial and muscle lactate concentrations, facilitating lactate steady state, thus 9 limiting differences in lactate diffusion capacity for the sprint and endurance trained.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to highlighting the importance of supplementing correlation coefficient analysis with LoA, these results also suggest greater reproducibility for individuals of greater aerobic fitness. Reproducibility of the 4.0 mmol·l -1 marker has also been reported for repeated incremental running 11 and cycling trials. 12 Recently, the measurement error of several markers was examined for the lactate-power relationship during incremental cycling of 3 min stages.…”
Section: Introductionmentioning
confidence: 91%